2021
DOI: 10.1016/j.envres.2021.111314
|View full text |Cite
|
Sign up to set email alerts
|

Indoor Air Quality Strategies for Air-Conditioning and Ventilation Systems with the Spread of the Global Coronavirus (COVID-19) Epidemic: Improvements and Recommendations

Abstract: The coronavirus has come to the world and spread with great wide among the countries of the world and has resulted in numerous infections that exceeded 110,518,566 million patients and are close to 2.5 deaths by September 2020. It also brought with it panic and fear, halted many activities, and led to the decline of the global economy. It changed human behavior and forced people to change their lifestyles to avoid infection. One of the most sectors that must be taken into consideration through pandemic coronav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
62
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(84 citation statements)
references
References 113 publications
0
62
0
1
Order By: Relevance
“…Studies have reported that adequate ventilation and appropriate HVAC systems can prevent the spread of the viruses; however, more research is required, particularly studies that assess ventilation in a non-hospital setting (Asanati et al, 2021;Kohanski et al, 2020;Ren et al, 2021). To err on the side of caution, some recommendations can be adapted from hospital rooms to other indoor facilities; these include (Elsaid and Ahmed, 2021) the provision of non-recirculated external air and which is changed at a high air changes per hour (ACH) (REHVA, 2021). The most effective solution is to decentralize ventilation, as this strategy has the benefit of securing the rooms where people do not stay (Guo et al, 2021;Hayashi et al, 2020).…”
Section: Research On Ventilation Of Rooms During the Covid-19 Pandemi...mentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have reported that adequate ventilation and appropriate HVAC systems can prevent the spread of the viruses; however, more research is required, particularly studies that assess ventilation in a non-hospital setting (Asanati et al, 2021;Kohanski et al, 2020;Ren et al, 2021). To err on the side of caution, some recommendations can be adapted from hospital rooms to other indoor facilities; these include (Elsaid and Ahmed, 2021) the provision of non-recirculated external air and which is changed at a high air changes per hour (ACH) (REHVA, 2021). The most effective solution is to decentralize ventilation, as this strategy has the benefit of securing the rooms where people do not stay (Guo et al, 2021;Hayashi et al, 2020).…”
Section: Research On Ventilation Of Rooms During the Covid-19 Pandemi...mentioning
confidence: 99%
“…According to hospital ventilation studies, it is necessary to ensure a large number of air changes per hour (Gettings et al, 2021). For a standard hospital ward, 12 ACH is recommended (Elsaid and Ahmed, 2021), and in other types of rooms it has been shown that 6.51 ACH ensures that the possibility of infection is kept below 1%; however, with the added conditions of proper mask adherence and a short exposure time (up to 3h) (Park et al, 2021). REHVA recommends 6-12 in hospitals, but generally, 5ACH should be used.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…The regression between PM 2.5 and AQI is strong every year (r 2 > 0.89 to r 2 < 0.96), however the lowest value recorded is in the post-COVID-19 period (r 2 = 0.89) (Figure 5). Since the COVID-19 pandemic, many scholars at home and abroad have discussed the characteristics of the changes in air quality under epidemic prevention and control, but relatively few studies have used statistical methods for their analysis [22,23]. In this study, a path analysis and a regression analysis were the main methods used to measure the relationships between the AQI value, the number of days of primary pollutant pollution, the pollutant concentration, and NO 2 /SO 2 , among other values, from January 2019 to Similarly, the regression between PM 10 and AQI is strong every year (r 2 > 0.87 to r 2 < 0.92), however the lowest value recorded is post-COVID-19 (r 2 = 0.87).…”
Section: Regression Analysis Implementationmentioning
confidence: 99%
“…Since the COVID-19 pandemic, many scholars at home and abroad have discussed the characteristics of the changes in air quality under epidemic prevention and control, but relatively few studies have used statistical methods for their analysis [22,23]. In this study, a path analysis and a regression analysis were the main methods used to measure the relationships between the AQI value, the number of days of primary pollutant pollution, the pollutant concentration, and NO 2 /SO 2 , among other values, from January 2019 to August 2021 and the same period in 2017 and 2018.…”
Section: Regression Analysis Implementationmentioning
confidence: 99%
“…Additionally, increasing indoor ventilation can effectively reduce indoor pathogenic microorganisms and viruses [39]. To increase the air volume of the filter in an existing HVAC system, we combined four plate-type micro-electrostatic filters together, and the airflow direction is shown in Figure 1a.…”
Section: Introductionmentioning
confidence: 99%